FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHATANI UBI JALAR (Ipomoea batatas L.) (Studi Kasus Pada Gapoktan “Nusa Bhakti” Desa Adinuso Kecamatan Reban Kabupaten Batang) - Umi Faidah; Endah Subekti; Shofia Nur Awami (MEDIAGRO, 2015)
The purposes of the research were to identify the factors that affected farmers'  income and to analysis the costs, revenues, income and feasibility level in terms of Break Even Point (BEP) and Revenue Cost Ratio (RC Ratio) on the sweet potato farming in Gapoktan “Nusa Bhakti” Adinuso Village, Reban District, Batang Regency. The method used was a case study in Gapoktan “Nusa Bhakti” Adinuso Village Reban District Batang Regency in Mei-September 2014 the planting season. The respondents were drawn using purposive sampling. Data collection was conducted using interview, observation, questionnaire and recording. The analysis method used in this research was descriptive analytical method. Data were analysed using multiple linear regression analysis. Primary and secondary data were analysed to yield answers on the research problems. The results showed that factors affecting the sweet potato farmers' income were sweet potato production, labour costs, the farmers' experience and the farmers' age. According to the data analysis, the total costs spent by farmers amounted to Rp 2,275,814.00/planting season, with a fixed cost of Rp 82,914.00/planting season and variable costs of Rp. 2,192,900/planting season. Whereas, the revenue amounted to Rp 4,702,626.00/planting season and income amounted to  Rp 2,426,812.00/planting season. The quantity BEP value was equal to 1,608 kg/planting season. Whereas, the rupiah BEP amounted to Rp 4,106,554/ planting season. The RC Ratio value in the sweet potato farming was 2.10.   Keywords: cost, income, revenue, sweet potato